Putting 600,000 Books Online: the Large-Scale Digitisation Partnership between the Austrian National Library and Google - Kaiser, Max (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2012)
In a public-private partnership with Google, the Austrian National Library is digitising its historical book holdings. Some 600,000 volumes from the sixteenth to the nineteenth centuries will be digitised and made available free of charge. The project demonstrates that public-private partnerships can be successful in enabling our heritage institutions to provide large-scale access to their holdings, provided that such partnerships are not exclusive and free access is ensured. The article outlines the preparatory phase and work flows established in the project.